PERANCANGAN BUKU ILUSTRASI PENANGANAN ANAK TANTRUM BAGI ORANG TUA - Fauzia, Fauzia; Marsudi, Marsudi (Universitas Negeri Surabaya, 2023)
Tantrum is a term for early childhood behavior that occurs due to their inability to control the overflow of emotions they feel, and difficulties in expressing their feelings and desires through words properly, which results in children crying, struggling, screaming, rolling around, throwing things and so on. This makes parents feel confused and frustrated about the actions taken by their children and creates negative attitudes, such as acts of violence through verbal or nonverbal which can disturb the child's mentality. The purpose of designing this illustration book is to provide information regarding tantrums and their handling, so that parents can address their child's tantrum behavior properly and correctly. This design uses a qualitative method which is carried out through several stages such as data identification, data collection through interviews, surveys, observation and literature studies, as well as through a Design Thinking approach in the form of empathize, define, ideate, prototype, and test, and there is a 5W1H needs analysis stage. The design of the concept of an illustration book that applies a digital cartoon style and contains concise, varied and colorful information, through a visualization process, and finalizes the design that produces an information medium in the form of an illustrated book on handling tantrums for parents, up to the implementation trial stage which was carried out on 5 parents, which is expected to become an information intermediary medium in providing additional insight regarding parenting with good results.